Hur kan PDOL vidareutvecklas? : En studie kring PDOL's image och experiencescape - Hedström, Elin; Lindberg, Viktoria (2011)
The purpose of this paper is to study the image and experiencescape of the festival “Piteå Dansar och Ler” (PDOL) and make suggestions for improvements. The word experiencescape describes the area within which a product or service is produced and consumed. Many of the festivals in Sweden went through a crisis during the years 2009-2010 and reported significant loss figures, but there were also some festivals that made profits. Our study object “Piteå Dansar och Ler” was one of the festivals that reported losses in the sums of million SEK in those years and was threatened with bankruptcy. They chose to continue and after making new structures within the organization the festival will be arranged in 2011. We have done surveys separately in 2007 and 2009, before a partnership had been raised. In the summer of 2007, the survey was out on PDOL's website (www.pdol.se) during a period of time after the festival, and a study was made on site during both day and evening from a visitor's perspective. Data were collected through observation and photography. In the year 2009 a questionnaire was handed out during the festival and a survey was also posted on PDOL's website. The results from both questionnaires showed that there is room for improvement of the festival, although many of the respondents rate PDOL as one of the best festivals in Sweden. Through the survey, we attempt to clarify how people perceive PDOL's image, and where there may be need for changes. We have also done a SWOT analysis from the surveys in which we attempted to clarify the strengths, weaknesses, opportunities and threats. Validerat; 20110726 (anonymous)